أمهات الكتب المتداولة في الدولة المرابطية وآثارها على الحركة العلمية 448-541هـ - بلول، ليلى, ضو، فاطمة (جامعة الوادي university of Eloued, 2021)
الملخص: تتناول هذه الدراسة التعريف بأمهات الكتب التي تم تداولها خلال العهد المرابطي بالمغرب والأندلس، من خلال آثارها على الحركة العلمية. وقد حصلت كتب العلوم الدينية واللغوية النصيب الكبير من الاهتمام بين العلماء والأمراء المرابطين، أما فيما يخص كتب العلوم العقلية فقد عرف الطب والصيدلة التقدم الملحوظ من خلال كتب جالينوس المتداولة، أما الكتب الفلسفية فقد عرفت تهميشا من جانب المرابطين إلا أنه كان من العلماء من إهتم بالفلسفة ودرسها وأبدع فيها. أما كتب علم التاريخ في عهدهم فازدهرت ازدهاراً يتناسب ومقامهم العلمي، وتم تداول كتب السير وخاصة كتب سيرة الرسول صلى الله عليه وسلم وكتب الطبقات والتراجم. عنوان المذكرة : أمهات الكتب المتداولة في الدولة المرابطية وآثارها على الحركة العلمية 448-541هـ. الكلمات المفتاحية: الدولة المرابطية، أمهات الكتب المتداولة، الكتب الدينية، الكتب اللغوية، كتب العلوم العقلية، كتب السير، كتب الطبقات . Summary: This study deals with the introducing of the most important books that were circulated during the Almoravid era in Morocco and Andalusia, through their effects on the scientific movement. Books of religious and linguistic sciences had received a great deal of attention among the Almoravid scholars and princes. As for the books of mental sciences, medicine and pharmacology knew remarkable progress through Galen’s books in circulation, whereas philosophical books were marginalized by the Almoravids. However ,there were scholars who were interested in philosophy, studied it and excelled in it. As for the books of history, they flourished in proportion to their scientific status during their reign, and biographies were circulated, especially books of the biography of the Messenger, peace be upon him, specialized biographies and biographies . The title of the thesis: The Circulating Reference Books in the Almoravid State And Their Effects On The Scientific Movement 448-541 H.
مذكرة ماستر تاريخ تخصص تاريخ الغرب الإسلامي في العصر الوسيط
Keywords: الدولة المرابطية، الكتب الدينية; État almoravide, livres religieux; Almoravid state, religious books